2021
DOI: 10.3390/en14133899
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Analysis of Potential Induced Degradation on Photovoltaic Cells, Regeneration and Artificial Creation

Abstract: Many photovoltaic (PV) parks suffer from a decrement in their generated power capability due to a phenomenon called potential induced degradation (PID). In this paper, a regenerative system using a high step-up DC–DC converter is proposed, for regenerating PV cells that have been degraded due to the PID effect. The same device also can be used for artificially creating PID on PV panels in order to study the effects of the PID under controlled conditions. The power converter offers multiple voltage levels at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Previous research [24,25], has suggested that the PID test can result in a nearly 20-30% drop in the output power, even for healthy PV modules. For the examined PV modules, the comparison between the output power loss at STC conditions before and after the PID test is shown in Figure 13, using an I-V curve illustration.…”
Section: Pid Testingmentioning
confidence: 99%
“…Previous research [24,25], has suggested that the PID test can result in a nearly 20-30% drop in the output power, even for healthy PV modules. For the examined PV modules, the comparison between the output power loss at STC conditions before and after the PID test is shown in Figure 13, using an I-V curve illustration.…”
Section: Pid Testingmentioning
confidence: 99%
“…Electronic devices often function at elevated temperatures and under operational voltages. [ 6,37,38 ] ICDs are therefore susceptible to heat and bias stress conditions. Additionally, PV modules are exposed to UV radiation due to their placement outdoors.…”
Section: Passivation Stability Of Ion‐charged Oxide Nanolayersmentioning
confidence: 99%
“…Electronic devices often function at elevated temperatures and under operational voltages. 31,42,74 Ion-charged dielectrics are therefore susceptible to heat and bias stress conditions. 31,42,74 Additionally, PV modules are exposed to UV radiation due to their placement outdoors.…”
Section: Stability Of Embedded Alkali Ionsmentioning
confidence: 99%
“…31,42,74 Ion-charged dielectrics are therefore susceptible to heat and bias stress conditions. 31,42,74 Additionally, PV modules are exposed to UV radiation due to their placement outdoors. Accelerated ageing experiments were carried out to determine how alkali ions at the Si-SiO 2 interface respond to such conditions.…”
Section: Stability Of Embedded Alkali Ionsmentioning
confidence: 99%